Poreformacki kościół pw. św. Michała Archanioła w Choczu.Dzieje, architektura i organizacja przestrzeni sakralnej, problematyka konserwatorska - Dąbkowska, Monika (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
The Order of Reformed Franciscans, a conservative and strict branch of Franciscans, flourished in Poland mainly on the territory of Wielkopolska and Małopolska. The convent in Chocz was chronologically the third foundation in the Wielkopolska custody. Its founder was bishop Andrzej Lipski, who in order to strengthen Catholicism not only brought the Reformed Franciscans to the place but also built a collegiate church, thereby creating a complex of religious institutions in one part of the town. In the years 1636-1639 there was a conflict between the Reformed Franciscans and the Bernardines. As a result the former were made to leave Chocz for a time. Upon return they began the construction of a new, brick church and convent (1699-1725 r.) It is worth noting that among others, Brother Mateusz Osiecki participated in the realization of the convent buildings. The church was erected in the recessed variant of the wall-pillar system and shows affinity to the Reformed Franciscan Church in Kalisz. Moreover, it is an important example of the sacral buildings of the Wielkopolska province of Reformed Franciscans. The convent was secularized in 1864 by decree of emperor Alexander II. The monks regained their right of ownership only in 1920. First, the convent buildings were used by the Order of Sisters the Shepherdesses of Divine Providence, and only later again by the Franciscans. At present the whole complex is under major restoration works.